A general approach for the site-selective modification of native proteins, enabling the generation of stable and functional antibody–drug conjugates12. Issue 3 (16th November 2018) - Walsh, Stephen J.; Omarjee, Soleilmane; Galloway, Warren R. J. D.; Kwan, Terence T.-L.; Sore, Hannah F.; Parker, Jeremy S.; Hyvönen, Marko; Carroll, Jason S.; Spring, David R.
Abstract : Divinylpyrimidine (DVP) linkers enable access to highly stable and functional antibody–drug conjugates. Abstract : Antibody–drug conjugates (ADCs) are a class of targeted therapeutics that utilize the specificity of antibodies to selectively deliver highly potent cytotoxins to target cells. Although recent years have witnessed significant interest in ADCs, problems remain with the standard linkage chemistries used for cytotoxin-antibody bioconjugation. These typically (1) generate unstable constructs, which may lead to premature cytotoxin release, (2) often give a wide variance in drug–antibody ratios (DAR) and (3) have poor control of attachment location on the antibody, resulting in a variable pharmacokinetic profile. Herein, we report a novel divinylpyrimidine (DVP) linker platform for selective bioconjugation via covalent re-bridging of reduced disulfide bonds on native antibodies. Model studies using the non-engineered trastuzumab antibody validate the utility of this linker platform for the generic generation of highly plasma-stable and functional antibody constructs that incorporate variable biologically relevant payloads (including cytotoxins) in an efficient and site-selective manner with precise control over DAR. DVP linkers were also used to efficiently re-bridge both monomeric and dimeric protein systems, demonstrating their potential utility for general protein modification, protein stabilisation or the development of other protein-conjugate therapeutics.